Na estranha ordem geométrica de tudo : as máquinas do Brasil - Pedro Rena Todeschi (2022)
Establishing as the research’s apex the conceptual-image of the “machine of the world”, con-ceived by Carlos Drummond de Andrade, alongside the “poetic of gaze” encrypted in his work, this dissertation – in a comparative gesture – aims to comprehend the new displays and configu-rations of the “machine of the world” throughout the contemporary domains of cinema, literature and visual arts. By employing the three conceptual-images that unfold from the “machine of the world” – the machine, the night and the present time, drawn out from Drummond’s poetics –, we seek to demonstrate how the commented works tackle Brazil’s current domination mecha-nisms (extractivism, labor exploitation, Google’s imperialism), as well as invent methods for subjective resistance picked up from the ordinary lives of common people, through minimal gestures that cut off the “machine of the world”. Hence, we examine a few works from visual artist and writers who address the new “machines of the word” (e.g. Laura Vinci, Rosângela Rennó, Eduardo Hargreaves and Nuno Ramos; Ricardo Aleixo, Marília Garcia and Veronica Stigger) and we pay special attention to the study of three Brazilian movies: Oswaldo Teixeira’s Erosões (2012), Affonso Uchôa and João Dumans’ Arábia (2017), and Ernesto Carvalho’s Nunca é noite no mapa (2016).